2012
DOI: 10.5601/jelem.2010.15.2.251-257
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fertilization on yield and quality of cultivar Kent strawberry fruit

Abstract: In an experiment carried out in 2006-2007, influence of different fertilizers on yield and quality of cv. Kent strawberry fruit was determined. Two combinations were tested, each consisting of 3 types of fertilizers. The control plants remained unfertilized. In both combinations, two types of multi-component fertilizers were used (T-5% N, 5% P 2 O 5 , 15% K 2 O and O-10% N, 5% P 2 O 5 , 10% K 2 O) as well as one rate of ammonium nitrate to provide 50 kg N ha-1 in the first combination and 70 kg N ha-1 in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
1
4
0
1
Order By: Relevance
“…However, B. velezensis application without AM fungi (control plants) affected the chemical properties of the fruit, such as TSS, pH, and TA, a phenomenon that can be influenced by the cultivar. This is also in agreement with the work of Chelpinski et al (2010), who reported that the application of azotobacter in the 'Chandler' strawberry cultivar had a major impact on some chemical properties of the fruit, such as TSS and total sugar. Likewise, the effect of biofertilizer on chemical properties was higher than the combined effect of AM fungi with B. velezensis.…”
Section: Resultssupporting
confidence: 82%
“…However, B. velezensis application without AM fungi (control plants) affected the chemical properties of the fruit, such as TSS, pH, and TA, a phenomenon that can be influenced by the cultivar. This is also in agreement with the work of Chelpinski et al (2010), who reported that the application of azotobacter in the 'Chandler' strawberry cultivar had a major impact on some chemical properties of the fruit, such as TSS and total sugar. Likewise, the effect of biofertilizer on chemical properties was higher than the combined effect of AM fungi with B. velezensis.…”
Section: Resultssupporting
confidence: 82%
“…Contradictory results were obtained concerning the effects of fertilization on antioxidant capacity in strawberries. Rate of ammonium nitrate was reported to influence antioxidant capacity (Chelpinski and others 2010). Low fertilization rates were shown to increase fruit flavonol and ellagic acid contents (Anttonen and others 2006), but increasing fertilizer rate and addition of compost were reported to increase the content of phenolics, flavonols, and anthocyanins (Wang and Lin 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the SSC/TA ratio was the focus of this study. Previous studies have shown that N, P, K, and water have significant effects on the yield and fruit quality of strawberry [27,[55][56][57][58]. We used a quadratic regression orthogonal rotation combination experimental design to investigate the optimal fertilization and water combination for high strawberry yield and best fruit quality (optimal SSC/TA ratio).…”
Section: Discussionmentioning
confidence: 99%